How Children of Color with Special Healthcare Needs Are Excluded from School and Community: A DisCrit Analysis - Amber Alaniz (International Journal of School Social Work, 2025)
Adverse childhood experiences (ACEs), child race, and child dis/ability status are all predictors of school exclusion (i.e., exclusionary discipline; e.g., suspension and expulsion) and community exclusion (e.g., involvement in the juvenile justice system, which isolates children from neighbors, family, and friends). The purpose of this paper is to examine the impact of ACEs on school or community exclusion for children of color with special health care needs (SHCN) or having one or more dis/ability or chronic physical, developmental, behavioral, or emotional conditions that require specialized health care and social services. Drawing on Disability Critical Race Theory, I describe each tenet as it relates to school and community exclusion among children of color with SHCN. Furthermore, social work as an entity has a core value to support self-expression and empathy for others—particularly for vulnerable and stigmatized populations.
Keywords: Race; Disability; Disability Critical Race Theory; ACEs